2006
DOI: 10.1128/aac.50.4.1222-1227.2006
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Pharmacokinetics and Pharmacodynamic Target Attainment of Ertapenem in Normal-Weight, Obese, and Extremely Obese Adults

Abstract: Little is known of the effects of obesity on ertapenem drug disposition and pharmacodynamics. Thirty healthy volunteers in three body mass index (BMI) groups (10 per group), normal weight (BMI, 18.5 to 24.9 kg/m 2 ), class I-II obesity (BMI, 30 to 39.9 kg/m 2 ), and class III obesity (BMI, >40 kg/m 2 ), were administered a 1-g dose of ertapenem. Serum concentrations were obtained over 24 h. Population pharmacokinetic data were obtained using a nonparametric adaptive grid followed by Monte Carlo simulation to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
66
2
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(77 citation statements)
references
References 20 publications
5
66
2
4
Order By: Relevance
“…A dose of 2 g twice daily of cefepime was insufficient to reach PD targets (17). Serum concentrations of ertapenem were lower in obese patients than in nonobese patients (18). Finally, the average steady-state serum concentration of TZP in a very obese septic patient was less than the concentration obtained in a healthy, nonobese population (19).…”
Section: Discussionmentioning
confidence: 89%
“…A dose of 2 g twice daily of cefepime was insufficient to reach PD targets (17). Serum concentrations of ertapenem were lower in obese patients than in nonobese patients (18). Finally, the average steady-state serum concentration of TZP in a very obese septic patient was less than the concentration obtained in a healthy, nonobese population (19).…”
Section: Discussionmentioning
confidence: 89%
“…Nevertheless, these data suggest that alternative agents with potentially greater in vitro potency and better tissue penetration should be investigated in special populations. For example, ertapenem has been previously shown to have favorable pharmacokinetics and achieve excellent PTAs against relevant bacteria across a wide range of body weights, including morbid obesity (45). These properties may be associated with reduced SSIs compared to those obtained with other pharmacodynamically less potent antibiotics, which may be more adversely effected by extremes of body weights (46)(47)(48).…”
Section: Discussionmentioning
confidence: 99%
“…Global surveillance studies have revealed that all carbapenems (ertapenem, imipenem, meropenem, and doripenem) are highly active against these resistant Enterobacteriaceae isolates (7,8,18). Recently, carbapenem-resistant Enterobacteriaceae isolates, particularly Klebsiella pneumoniae carbapenemase-producing K. pneumoniae (KPC-KP) and New Delhi metallo-␤-lactamase-1 (NDM-1)-producing Enterobacteriaceae have emerged in many countries as a result of intracontinental and intercontinental spreading (3-6, 20, 23, 25, 27, 31, 32, 34, 35, 38).…”
mentioning
confidence: 99%